ANALYSIS OF HOT WATER HEATERS FOR INDIVIDUAL HEATING STATION WHEN THE TEMPERATURE CHART OF THE DISTRIBUTION HEAT NETWORK IS CHANGED - Aleksahin, А.; Boblovskii, А.; Kruhliakova, О.; Chaika, Y. (Municipal economy of cities (Technical science), 2023)
The aspects of the functioning of centralized heating systems of residential urban districts after additional insulation of this district existing buildings were considered. The influence of the heat carrier temperature in the district distribution heating network on the heat transfer surface of the heat exchangers that are installed in the individual heat station schemes for hot water supplying was analyzed. Estimates were made for single-stage connection of the heat exchangers to the heating systems. When determining the heat transfer surface, known criterion equations for plate heat exchangers of heat supply systems were used. The range of changes in the heat transfer surface of hot water heaters and the consumption of network water is determined depending on the selected temperature chart of the distribution heat network. The proposed recommendations can be useful in developing a heat supply quality control schedule for a district buildings heating systems in a district when the building thermal insulation process is completed. Possible approaches to the thermal design of heat exchangers of the hot water supply system for insulated buildings individual heating stations are considered when changing the temperature chart of the district heating supply system of the residential urban districts. Estimates were made to understand the influence of the reduced temperature chart for heat supply of the districts on the network water consumption for hot water heating and the surface of heat exchangers of insulated buildings heaters. It was shown that the increase in network water consumption for building hot water supply can be 1.5 to 3 times higher. The analysis presented for the surface of the heat exchangers of heating installations for insulated buildings hot water supply shows that it can be even double increase of heaters heat transfer surface depending on the temperature chart. The results obtained should be taken into account when planning the temperature chart of the heat carrier for a distribution heating network.